Catalytic Asymmetric Synthesis of Allylic Alcohols and Derivatives and their Applications in Organic Synthesis. Issue 7 (14th January 2013) - Lumbroso, Alexandre; Cooke, Michael L.; Breit, Bernhard
Abstract Allylic alcohols represent an important and highly versatile class of chiral building blocks for organic synthesis. This Review summarizes the plethora of methods developed for the catalytic asymmetric synthesis of enantioenriched allylic alcohols. These include: dynamic kinetic resolution (DKR/DKAT), nucleophilic 1, 2‐addition to carbonyl groups, allylic substitution, oxidation of CH bonds, the addition of O nucleophiles to π systems, reduction of unsaturated carbonyl compounds, and an alternative route from enantioenriched propargylic alcohols. Furthermore, these catalytic asymmetric processes are exemplified by their applications in the syntheses of complex molecules such as natural products and potential therapeutic agents.